Effects of dietary chromium picolinate supplementation on egg production, egg quality and serum concentrations of insulin, corticosterone, and some metabolites of Japanese quails - Şahin, Kazım; Küçük, Ömer; Şahin, Nurhan; Ozbey, O (Pergamon-Elsevier Science Ltd, 2001)
The effect of chromium (chromium picolinate, CrPic) supplementation on egg production, egg quality and serum concentrations of insulin, corticosterone and some metabolites of Japanese quails (Coturnix coturnix japanica) was evaluated. One hundred and fifty laying Japanese quails (45-d-old) were divided into five groups, 30 birds per group. The quails were fed either a control diet containing 1285.96 mug chromium (Cr)/kg, of diet or the control diet supplemented with either 200 mug of Cr/kg, of diet, 400 mug of Cr/kg of diet, 800 mug of Cr/kg of diet or 1200 mug of Cr/kg of diet. Increased supplemental chromium resulted in an increase in body weight (P = 0.05, linear), feed intake (P = 0.05, linear), ego, production (P = 0.01, linear), and also improved feed efficiency (P = 0.01, linear). Increased supplemental chromium decreased (P = 0.05, linear) egg shape index, whereas linearly increased egg weight (P = 0.01), eggshell weight (P = 0.01), eggshell thickness (P = 0.01), albumen index (P = 0.01), albumen weight (P = 0.05), yolk index (P = 0.05),yolk weight (P = 0.01), and egg specific gravity (P = 0.05). Serum insulin concentration linearly increased (P = 0.01), whereas corticosterone concentration linearly decreased (P = 0.05) as dietary chromium supplementation increased. Serum glucose and cholesterol concentrations decreased (P = 0.01), while protein concentrations increased linearly (P = 0.001) with higher dietary chromium supplementation. The results of the present study show that chromium supplementation, particularly at 1200 ppb, increases the performance, egg quality, and serum insulin concentrations of Japanese quails. (C) 2001 Elsevier Science Inc. All rights reserved.
Keywords: chromium; egg; insulin; corticosterone; Japanese quail